The Relationship Between Work Motivation and Job Satisfaction: A Meta-Analysis Study - Ananda Putri; Alvira Roslia; Alif Naafi Ardradhika (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Job satisfaction is an attitude and feeling where an employee enjoys and feels happy for all roles and achievements in their work. Various kinds of research on job satisfaction have been done and one of them is work motivation has a relationship with job satisfaction. This study aims to analyze the relationship between work motivation and job satisfaction. The research method used is meta-analysis with secondary data sources. A total of 27 pieces of literature discussing the relationship between work motivation and job satisfaction in the last 10 years have been collected from index databases such as Emerald, ScienceDirect, Elsevier, Google Scholar, SINTA and Garuda Portal. The data were analyzed using correlation meta-analysis with the help of the Meta-Mar online website. The results show that the correlation value of random effect size (I2 = 95%) is .519 (95% CI = .437; .715) with a significance value of .001 (p-value < .05), which means that a large effect size exists. Therefore, work motivation and job satisfaction have a significant and strong relationship. The Rosenthal Fail-safe Number value is 7739 (F-s N > 5K+10), which means that this study is free from publication bias.